Aprendizagem cotidiana em escritórios de arquitetura - Glaucinei Rodrigues Correa (2014)
In this thesis, it approaches the daily production of projects in architectural firms, aiming to reveal how people learn to do/develop such projects in practice. For this relate two anthropological approaches to learning making projects: a "situated learning" by Jean Lave and "constitution of skill" by Tim Ingold. The focus of the study of learning proposed here focuses on practices that lead the beginner to understand the process based on relationships with other learners and more experienced, unlike the studies that investigate learning in the classroom - that focus on teaching practices, revealing the ways in which design is taught (the teaching). The research was conducted in two architectural firms, including the analysis of project management systems, aiming tounderstand the functioning of the offices; everyday observation of production projects, to understand the practices of everyday life and people's participation in the project; interviews, in order to seek information not perceived in the observation and show how issues related to the production of projects were seen by the people involved in the process. The life history of the individuals pointing participation in contexts that involve the architecture prior to the academic education and practice of architecture from the first half of the course. It was noticed that the daily work in architectural offices there are multiple situations that promote learning and that architects learn from these practices specific environments, such as the manipulation of models (file-reference),validation/evaluation of the project and participation in the project review meetings. Among these practices, repetition, observation and peer relationship underlying the learning process. Stand out from the access and participation regulate the daily practices of learning the process of making architectural designs and what is seen in everyday life is the integration and interaction between people; are processes of learning (not teaching). These practices reiterate the idea that learning to project is a complex activity that learning is a process of changing practices and of persons and, above all, that learning is a more relational activity (collective) than individual. They show, too, to learn to do architectural projects is an ongoing process, slow and requires many years of practice. The skills of the architects are constituted in these environmentsand, therefore, have nothing innate. These practices are experienced and learned day by day, are processes of "rediscovery". The processes and procedures of project managementin addition to regular, standardize and help control project development process, collaborate so that people learn in these environments. The contributions of this research can serve to architects, teachers, teachers-architects and students. The main one brings up these practices, which are often invisible and in some cases even underestimated, but that reveal how a beginner becomes architect daily in these environments.